Sistem Informasi SMP Negeri 5 Walenrang Berbasis Web - Saputra, Wahyu; Apriyanto, A; Paembonan, Solmin (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2022)
This study aims to create and implement a web-based information system for SMP Negeri 5 Walenrang. The type of research used in this study is Research And Development (R&D) with data collection techniques using observation methods, documentation methods, and interview methods. The web-based information system of SMP Negeri 5 Walenrang is designed using the UML (Unified Modeling Language) model which consists of use case diagrams, activity diagrams, sequence diagrams and class diagrams. The information system that is built is web-based using the PHP programming language and MySQL database. The results of this information system are login page, profile input page, news publication input page, agenda input page, activity schedule input page, news input page, student input page, lesson input page, input page, grades, lesson input page, input page schedule, home page, profile page, news publication view page, agenda page, gallery page, grade view page, schedule view page, teacher data page. This system has been tested using black box testing, where all tested displays are guilty as desired